2015
DOI: 10.4103/2229-5151.152324
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of magnesium sulphate and nitroglycerine as potential adjuncts to lidocaine in intravenous regional anaesthesia

Abstract: Introduction:This randomized control trial was carried out to evaluate and compare the efficacy of magnesium sulphate and nitroglycerine (NTG) as adjuncts to lidocaine in intravenous regional anesthesia (IVRA).Materials and Methods:Seventy-five, ASA grade I and II patients, aged between 20–50 years, scheduled for hand and forearm surgery were selected and entered randomly into three study groups. Patients in group C received 3 mg/kg of preservative free lidocaine 2% diluted with saline to a total volume of 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A similar study showed that addition of magnesium sulphate and nitroglycerine to lignocaine for IVRA leads to early onset of sensory block. 7 A study was done where magnesium sulphate as an adjunct to lignocaine for IVRA shorten the onset of sensory and motor block. 8 In our study we observed that the total dose of lignocaine required to achieve surgical anaesthesia was significantly lower in magnesium group compared to the saline group.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that addition of magnesium sulphate and nitroglycerine to lignocaine for IVRA leads to early onset of sensory block. 7 A study was done where magnesium sulphate as an adjunct to lignocaine for IVRA shorten the onset of sensory and motor block. 8 In our study we observed that the total dose of lignocaine required to achieve surgical anaesthesia was significantly lower in magnesium group compared to the saline group.…”
Section: Discussionmentioning
confidence: 99%
“…[18] used 150 mg of MgSO 4 in supraclavicular brachial plexus block, whereas Bansal et al . [19] used 1.5 g of MgSO 4 in intravenous regional anaesthesia (IVRA), without any reported side effect and neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study were in accordance with a study by Bansal et al . [19] In another study,[18] no statistical significance was observed in the onset time of sensory and motor block with magnesium (150 mg) used as an adjuvant to ropivacaine. This could be because the larger volume of local anaesthetic (30 ml) used in the study lead to a reduced effective concentration of magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Bansal et al [14], compared the effect of adding 1.5 gram magnesium sulphate versus 200 µg nitroglycerin as adjuvant to lidocaine in intravenous regional block on seventy-five patients scheduled for hand and forearm surgeries and they found that both of magnesium and nitroglycerin accelerated the onset of sensory and motor block, prolonged the duration of sensory and motor block, and decreased the postoperative analgesic request without any side effects.…”
Section: Tablementioning
confidence: 99%